Peningkatan Pengetahuan dan Ketrampilan Kader melalui Pelatihan Konseling Menyusui di Puskesmas Nania Kota Ambon - Ety Yuni Ristanti; Michran Marsaoly; Muhamad Asrar; Sitti Suharni Hermanses (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
The low coverage of exclusive breastfeeding is due to the lack of public understanding of the benefits and importance of exclusive breastfeeding for infant aged 0–6 months, so it is necessary to empower posyandu cadre as breastfeeding counsellor who provide counselling for mothers to Nania health center as counsellor breastfeeding. The purpose of this study is to improving the knowledge and skills of cadres through counseling training of breastfeeding at Nania Health Center Ambon. The community service partner is Nania Health center. The method used is training, assistance, monitoring and evaluation. The number of cadres trained was 40 people. The training took place at Nania health care, on 23–27 October 2019. There was an increase in the knowledge level of cadres about breastfeeding after being given breastfeeding counseling training, where most of the knowledge levels were good (67.5%). Cadres are skilled in providing breastfeeding counselling to mothers who have babies aged 0-6 months or pregnant women.